2012
DOI: 10.1111/j.1747-1346.2011.00341.x
|View full text |Cite
|
Sign up to set email alerts
|

Political and Social Dimensions of Civic Engagement: The Impact of Compulsory Community Service

Abstract: In 1999, the Canadian province of Ontario joined a number of other jurisdictions in requiring its high school students to complete volunteer service before graduating. The primary objective of this program, and others like it around the world, was to address declining civic engagement within society. Using a quasi-experimental design, we explore the impact of mandatory volunteering on its stated aims. Our findings suggest that volunteering in high school has positive impacts on the political dimensions of a st… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
18
0

Year Published

2016
2016
2023
2023

Publication Types

Select...
5

Relationship

1
4

Authors

Journals

citations
Cited by 16 publications
(19 citation statements)
references
References 64 publications
1
18
0
Order By: Relevance
“…Our findings support the general thesis that performing community service in secondary school is related to the likelihood of performing service in subsequent years. However, consistent with previous studies of the Ontario student population conducted one year (Henderson et al ) and two years (Henderson et al ) after their graduation, the present study, conducted four years out, found that service in secondary school was not by itself enough to predict subsequent volunteering. In previous studies only service recalled as satisfying and/or of some duration (a year or more) was associated with a greater likelihood of future volunteering.…”
Section: Discussionsupporting
confidence: 86%
See 1 more Smart Citation
“…Our findings support the general thesis that performing community service in secondary school is related to the likelihood of performing service in subsequent years. However, consistent with previous studies of the Ontario student population conducted one year (Henderson et al ) and two years (Henderson et al ) after their graduation, the present study, conducted four years out, found that service in secondary school was not by itself enough to predict subsequent volunteering. In previous studies only service recalled as satisfying and/or of some duration (a year or more) was associated with a greater likelihood of future volunteering.…”
Section: Discussionsupporting
confidence: 86%
“…Previous studies of the Ontario programme have suggested that positive effects are conditional on the service experience being sustained and evaluated positively by students (Henderson et al ), that positive evaluations are tied to individual and community benefits, including altruism, personal fulfilment, personal and career development (Henderson et al ) . In addition to the effects on subsequent service, mandated service appears to have a positive effect on the political dimensions of civic engagement (including political involvement and activity) rather than social dimensions, but that these effects are also conditional on duration and the perceived quality of the service experience (Henderson, Brown and Pancer ).…”
Section: Introductionmentioning
confidence: 99%
“…Besides these societal benefits, youth volunteering has also been associated with personal gains in self-esteem (Conrad and Hedin 1982; Johnson et al 1998; Yogev and Ronen 1982), social skills (e.g., communication, leadership, and problem solving) (Celio et al, 2011; Conrad and Hedin, 1982), social capital (Flanagan et al, 2015), and academic motivation and performance (Celio, Durlak, and Dymnicki 2011; Conway, Amel, and Gerwien 2009). Moreover, some exceptions notwithstanding (Helms, 2013; Stukas et al, 1999; Warburton and Smith, 2003), researchers have reported that required service can yield similar benefits as voluntary service, especially if it is sustained and of high quality (Flanagan et al 2015; Hart et al 2007; Henderson et al 2007; Henderson, Brown, and Pancer 2012; Metz and Youniss 2003, 2005). …”
Section: Introductionmentioning
confidence: 99%
“…Comparing three successive classes of students in a Boston high school, one without and two with a community service requirement, Metz and Youniss (2003, 2005) found that mandated community service did not have significant effects on students already inclined to volunteer, but increased less-inclined students’ intentions to vote and volunteer in the future. Likewise, in a series of studies on the mandatory community service program implemented by the Ontario provincial government in 1999, Henderson and colleagues (Henderson et al, 2014, 2012, 2007) found no significant differences between students from mandated and non-mandated cohorts regarding their civic attitudes and behaviors in the short run. The authors concluded that mandatory programs can have a positive effect on subsequent civic engagement, especially if they demand long-term commitment from students and produce positive experiences.…”
Section: Introductionmentioning
confidence: 99%
“…Further, Maldonado (2014) finds that, in Ecuador and Peru, those who are less engaged in politics are most likely to support the abolition of compulsory voting. 26 Research on mandatory community service provides evidence reflective of such a pattern; individuals who are conscripted into community service that would not have served voluntarily do not become more civically engaged and become less likely to serve again (Henderson, Brown, and Pancer 2012;Stukas, Snyder, and Clary 1999).…”
Section: Compulsory Voting and The Effects Of Coercion And Punishmentmentioning
confidence: 99%